The Effects of Construction Stage on the Development of Retaining Wall - Voo,Kien Hiung (School of Environmental Engineering, University Malaysia Perlis, 2016)
To analyze the deformation of soil during construction stages. To analyze the displacement of the retaining wall. To analyze the stability of diaphragm wall and sheet pile wall.